Reproduksi Poligami Tidak Tercatat: Layanan Nikah Tidak Tercatat dan Simplifikasi Perkawinan - Ahmad Faisal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This research presents an analysis of the phenomenon of unregistered polygamy reproduction that occurs in the region of Gorontalo. The research recognizes the issue as being counter-productive to the government's efforts to regulate the administration of citizens' marriages. To gain a deeper understanding of the problem, a qualitative research method was employed, incorporating aspects of observation, interviews, and documentation. The results show that unregistered polygamy is rising due to sociological and epistemological factors, such as the availability of unrecorded marriage services and a simplified view of avoiding adultery. Therefore, he increasing unregistered polygamy reproduction is not caused by strict government regulations or difficult official agency services but more due to pragmatic and simplistic reasons. However, this trend of unregistered polygamy will persist unless addressed through education, advocacy, socialization, and correction efforts.